Gain of transcription factor binding sites is associated to changes in the expression signature of human brain and testis and is correlated to genes with higher expression breadth - Silva, Vandeclécio Lira da (2019)
The gain of transcription factor binding sites (TFBS) is believed to represent one of the major causes of biological innovation. Here we used strategies based on comparative genomics to identify 21,822 TFBS specific to the human lineage (TFBS-HS), when compared to chimpanzee and gorilla genomes. More than 40% (9,206) of these TFBS-HS are in the vicinity of 1,283 genes. A comparison of the expression pattern of these genes and the corresponding orthologs in chimpanzee and gorilla identified genes differentially expressed in human tissues. These genes show a more divergent expression pattern in the human testis and brain, suggesting a role for positive selection in the fixation of TFBS gains. Genes associated with TFBS-HS were enriched in gene ontology categories related to transcriptional regulation, signaling, differentiation/development and nervous system. Furthermore, genes associated with TFBS-HS present a higher expression breadth when compared to genes in general. This biased distribution is due to a preferential gain of TFBS in genes with higher expression breadth rather than a shift in the expression pattern after the gain of TFBS.